Comparative Study on Oven and Solar Drying of Agricultural Residues and Food Crops - Mehmood Ali; Fazeela Niazi; Mubashir Ali Siddiqui; Muhammad Saleem (International Journal of Renewable Energy Development, 2022)
The current study examined reduction of moisture from agricultural energy and food crops in a conventional oven to a solar dryer at various treatment periods at temperature between 40 ± 10 oC.  Sugarcane bagasse and Phragmites Australis had initial moisture of 50.8 % and 6.07 % by dry weight, respectively, with higher heating values (HHV) 6548.5 kJ/kg and 17653.02 kJ/kg respectively. The moisture content of bagasse and phragmites were decreased by 51.31% and 68.69% respectively using oven drying, while the moisture content of bagasse and phragmites was reduced by 48.01% and 66.22% respectively, using solar drying with 5 hrs treatment time. Corresponding increase in HHV’s observed in bagasse to 11195.6 KJ/kg (oven drying) and 10998.1 KJ/kg (solar drying), while HHV of phragmites increased to 18706.79KJ/kg (oven drying) and 18685.36KJ/kg (solar drying). Green chillies had a moisture content reduction by 33.69 % (oven) and 8.28 % (solar), whereas grapes had a reduction by 31.20 % (oven) and 7.88 % (solar) with 5 hrs treatment time. The oven drying approach revealed higher carbohydrate content in food crops when compared to solar drying, while both treatments showed a similar drop in protein, fat, and vitamin C contents. Statistical and energy analysis observed that comparing solar drying; the oven drying eliminates slightly higher moisture content and have less drying energy requirements.  The amount of heat energy required for drying unit mass of bagasse was 0.476 kJ/kg (oven) and 0.556 kJ/kg (solar), for phragmites it was 0.074 kJ/kg (oven) and 0.092 kJ/kg (solar), for chilles 0.524 kJ/kg (oven) and 0.576 kJ/kg (solar) and for grapes 0.123 kJ/kg (oven) and 0.157 MJ/kg (solar). According to the results solar drying required greater quantity of heat energy than oven drying. Mass transfer analysis showed drying constant of bagasse and phragmites were higher initially, then showed reducing trend with respect time. Furthermore, it was observed that the effective diffusivity and mass transfer coefficient were found reducing with respect to increasing drying treatment time. The research findings of renewable solar drying, on the other hand, are comparable to those of oven drying, demonstrating that there is still enough untapped heat energy available for its utilization in biomass thermo-chemical conversion methods.